2013
DOI: 10.1016/j.physbeh.2013.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Appetitive traits from infancy to adolescence: Using behavioral and neural measures to investigate obesity risk

Abstract: We come into the world with enduring predispositions towards food, which interact with environmental factors to influence our eating behaviors and weight trajectories. But our fates are not sealed – by learning more about this process we can identify ways to intervene. To advance this goal this we need to be able to assess appetitive traits such as food cue responsiveness and satiety sensitivity at different developmental stages. Assessment methods might include behavioral measures (e.g. eating behavior tests,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
59
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 120 publications
8
59
1
2
Order By: Relevance
“…neuro-imaging techniques, laboratory-based behavioral tasks, and questionnaires that measure RS to all kinds of reward, i.e. 'general RS', as well as specifically to palatable food reward (Carnell, Benson, Pryor, & Driggin, 2013). To use the information on this association for preventive purposes, the RS measure needs to be easily and practically applicable, and inexpensive; therefore, it is advisable to use questionnaires.…”
Section: Introductionmentioning
confidence: 99%
“…neuro-imaging techniques, laboratory-based behavioral tasks, and questionnaires that measure RS to all kinds of reward, i.e. 'general RS', as well as specifically to palatable food reward (Carnell, Benson, Pryor, & Driggin, 2013). To use the information on this association for preventive purposes, the RS measure needs to be easily and practically applicable, and inexpensive; therefore, it is advisable to use questionnaires.…”
Section: Introductionmentioning
confidence: 99%
“…These measures are based on the biological mechanisms of appetite regulation. The most commonly used procedures are the biological (short- and long-term appetite regulation biomarkers [3] and magnetic resonance techniques, able to detect variations in blood flow in response to neuronal activity [68]) and behavioural methods (laboratory observation and psychometrics).…”
Section: Appetite and Related Eating Behaviours Assessmentmentioning
confidence: 99%
“…These techniques are based on the detection of changes in blood flow associated with neuronal activation [68]. It has been suggested that obese individuals experienced greater reward from food consumption and anticipated food intake than lean individuals using functional magnetic resonance imaging [69, 70].…”
Section: Appetite and Related Eating Behaviours Assessmentmentioning
confidence: 99%
See 2 more Smart Citations